Pengaruh Intensitas Penggunaan Media Sosial Instagram Terhadap Tingkat Kepercayaan Diri - Rizqi Oktaviani; Didi Permadi; Diryo Suparto (TUTURAN: Jurnal Ilmu Komunikasi, Sosial dan Humaniora, 2023)
English translation. Instagram is one of the social media in Indonesia that is very popular and widely used by people from various circles. Instagram users in Indonesia by gender are dominated by women, which is 52.6%. While in terms of age, the age group of 18-24 years is the largest user group of 32 million users. Instagram has various advantages in terms of features and appearance that make users feel comfortable and at home for a long time playing Instagram. As a photo and video-based social media, it allows Instagram users, especially women, to compare themselves with others who seem superior to them on Instagram. If this is done continuously, it allows Instagram users to experience mental health disorders such as loss of confidence. This study discusses the effect of the intensity of Instagram social media use on the level of self-confidence among FISIP students of Pancasakti Tegal University using quantitative methods. The research approach in this study is a quantitative approach with survey methods. The population in this study was all FISIP female students who used Instagram, while the number of research samples was 74 female students. Data acquisition is obtained through the distribution of questionnaires. Questionnaire questions refer to research indicators and uses and effect theory. The results obtained in this study are that the working hypothesis (H1) is accepted and the null hypothesis (H0) is rejected, because there is an influence of the intensity of Instagram social media use on the level of self-confidence among FISIP students of Pancasakti Tegal University. The resulting effect was 23.6% with a degree of relationship between moderately correlated variables.